2021
DOI: 10.1016/j.aninu.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with curcumin-loaded nanocapsules in lambs: Nanotechnology as a new tool for nutrition

Abstract: Curcumin-containing nanocapsule powder formulations have not been used in ruminant feed to date, despite the fact that curcumin is known to be a functional food additive. The objective of this study was to determine whether ethyl polymethacrylate (Eudragit L-100) nanocapsules loaded with curcumin (N-CU) would improve health and growth of lambs. Thirty-two male Lacaune lambs (body weight [BW] = 16 ± 0.99 kg; 45 d of age) were randomly assigned to 1 of 4 treatments: T0, T1, T2 and T4, representing supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
11
7
0
Order By: Relevance
“…This can be explained by the possibility that the doses of CN were non-hazardous to the health status and did not affect the digestibility in terms of carbohydrate (amylase, AMYL enzyme activity) and lipid (lipase, LYPS enzyme activity) metabolism. In consistency with our study, Marcon et al [31] reported that the young lambs fed 1 mg/kg diet of curcuminloaded nanocapsule did not show any significant changes in serum GLU and GGT levels compared to the control diet. Serum TBIL, ALT, AST, and ALKP are the indicators of liver function where higher levels of these parameters indicate deleterious conditions of the body.…”
Section: Serum Biochemistry Of Pigletssupporting
confidence: 93%
See 4 more Smart Citations
“…This can be explained by the possibility that the doses of CN were non-hazardous to the health status and did not affect the digestibility in terms of carbohydrate (amylase, AMYL enzyme activity) and lipid (lipase, LYPS enzyme activity) metabolism. In consistency with our study, Marcon et al [31] reported that the young lambs fed 1 mg/kg diet of curcuminloaded nanocapsule did not show any significant changes in serum GLU and GGT levels compared to the control diet. Serum TBIL, ALT, AST, and ALKP are the indicators of liver function where higher levels of these parameters indicate deleterious conditions of the body.…”
Section: Serum Biochemistry Of Pigletssupporting
confidence: 93%
“…According to the ALT and ALKP data in our study, it seemed that higher levels of ALT and ALKP were not toxic to the liver, as reflected by the increment of growth with a significantly higher weight gain in the T2 group compared to the control diet. In consistency with the present study, Marcon et al [31] found a significantly higher level of AST in lambs fed 2 mg/kg diet of curcumin-loaded nanocapsule compared with the control diet. Likewise, Reda et al [45] reported that dietary nanocurcumin at 0.5 g/kg of diet could significantly increase the ALT level in Japanese quails as a monogastric animal model, in agreement with the present study.…”
Section: Serum Biochemistry Of Pigletssupporting
confidence: 93%
See 3 more Smart Citations